Gambaran Stres pada Adult-Child Caregiver dalam Merawat Orang Tua dengan Penyakit Pikun - Shafiya Nisrina; Nadhirotul Laily; Asti Candrasasi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
There are currently more than 55 million people suffering from senile worldwide, more than 60% of whom are dominated by middle and low income countries. Every year, 10 million cases of senile occur. Senile is caused by various diseases that attack the brain. Alzheimer's disease is one of the most common forms of this disease and can cause 60-70% of cases in elderly people with senile. Caring for a parent with senile has the potential to be very stressful. The aim of this research is to determine the description (aspects, levels, & influencing factors) of stress in adult-child caregivers in caring for parents with senile. The method used in this research is qualitative with a phenomenological type. The subjects in this study were 3 people who played the role of Adult-Child Caregiver for a period of 4 years or more. The data collection technique uses the interview method. The data analysis technique uses the Miles and Hubberman model. The data credibility techniques used are source triangulation and member checking. The results of this research show that there is a description of the stress experienced by the subject with both biological and psychological aspects. 2 of the 3 subjects studied had Very Severe Stress levels with the influence of economic, family and environmental factors. 1 in 3 subjects have symptoms of excessive stress and have experienced it for a very long time. The results of this research can be a suggestion for other adult-child caregivers to receive training to increase their skills in caring for elderly parents.